Synthesis of Co(ll), Ni(ll), Cu(ll), Pd(ll), and Pt(lV) Complexes with 14,15,34,35-Tetrahydro-11H, 31H-4,8-diaza-1,3(3,4)-ditriazola-2,6(1,4)-dibenzenacyclooctaphane-4,7-dien-15,35-dithione, and the Thermal Stability of Polyvinyl Chloride Modified Complexes - Ali Mudher Abdulkareem Al-Khazraji (Indonesian Journal of Chemistry, 2023)
In the current endeavor, a new Schiff base of 14,15,34,35-tetrahydro-11H,31H-4,8-diaza-1,3(3,4)-ditriazola-2,6(1,4)-dibenzenacyclooctaphane-4,7-dien-15,35-dithione was synthesized. The new symmetrical Schiff base (Q) was employed as a ligand to produce new complexes comprising Co(II), Ni(II), Cu(II), Pd(II), and Pt(II) metal-ions at a ratio of 2:1 (Metal:ligand). There have been new ligands and their complexes validated by (FTIR), (UV-visible), 1H-NMR, 13C-NMR, CHNS, and FAA spectroscopy, Thermogravimetric analysis (TG), Molar conductivity, and Magnetic susceptibility. The photostabilization technique to enhance the polymer was also used. The ligand Q and its complexes were mixed in 0.5% w/w of polyvinyl chloride in tetrahydrofuran (THF). The photo stabilization of polymer films was studied at 25 °C under irradiation of light λ 380–250 nm with intensity of 7.75 × 10−9 ein dm−3 s−1. The photostabilization activity of these compounds was determined by monitoring the hydroxyl, carbonyl, and polyene indexes, weight loss method with irradiation time. The ICO, IPO and IOH index values increased with irradiation time, this increase depends on the type of additives. The surface morphology for these films was studied during irradiation time. This project is highly intriguing for the ecosystem in regards to the decrease in the consumption of plastic.